2014
DOI: 10.1002/2013wr013578
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic coupling in microbially mediated fracture mineralization: Formation of self-organized groundwater flow channels

Abstract: [1] Evidence of fossilized microorganisms embedded within mineral veins and mineralfilled fractures has been observed in a wide range of geological environments. Microorganisms can act as sites for mineral nucleation and also contribute to mineral precipitation by inducing local geochemical changes. In this study, we explore fundamental controls on microbially induced mineralization in rock fractures. Specifically, we systematically investigate the influence of hydrodynamics (velocity, flow rate, and aperture)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 76 publications
(93 reference statements)
2
52
0
Order By: Relevance
“…The lack of significant changes to DOM composition found here support those of a previous modeling study at the Krycklan sites, which estimated that maximum levels of in-stream DOC losses are not likely greater than 0.09 mg L À1 during base flow (i.e., 0.5% of mean base flow [DOC]), when maximum stream water residence times would be 2 days [Tiwari et al, 2014]. Across the full Krycklan catchment (68 km 2 ), stream water residence times vary from a mere 6 h during peak flow, to a maximum of 2 days at base flow [Tiwari et al, 2014]. At this short time scale, and given the small loss of total DOC relative to substantial background concentrations (mean 20.7 ± 7.3 mg L À1 ), it is not surprising that we found negligible in-stream changes to the composition of DOM.…”
Section: Discussionsupporting
confidence: 86%
“…The lack of significant changes to DOM composition found here support those of a previous modeling study at the Krycklan sites, which estimated that maximum levels of in-stream DOC losses are not likely greater than 0.09 mg L À1 during base flow (i.e., 0.5% of mean base flow [DOC]), when maximum stream water residence times would be 2 days [Tiwari et al, 2014]. Across the full Krycklan catchment (68 km 2 ), stream water residence times vary from a mere 6 h during peak flow, to a maximum of 2 days at base flow [Tiwari et al, 2014]. At this short time scale, and given the small loss of total DOC relative to substantial background concentrations (mean 20.7 ± 7.3 mg L À1 ), it is not surprising that we found negligible in-stream changes to the composition of DOM.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Garcia-Rios et al (2017) showed that the presence of small-scale mineral heterogeneities increased the reaction potential of a sandstone core by limiting the development of wormholes. Similarly, when reactions lead to mineral precipitation, mineral heterogeneity can lead to variations in local reaction rates that enhance preferential flow (Jones & Detwiler, 2016;Mountassir et al, 2014), which does not occur in fractures with uniform surface mineralogy (Hilgers & Urai, 2002;Hilgers et al, 2003;Lee & Morse, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, in many subsurface environments, fluid-rock interactions lead to mineral precipitation, which can significantly reduce fracture permeability. This fracture sealing process can have the desired effect of enhancing the ability of geologic seals to isolate, for example, overpressurized CO 2 [Huerta et al, 2013;Matter et al, 2016], hydrocarbons [Boles et al, 2004], or hydrothermal fluids [Chaudhuri et al, 2012] and may be enhanced by microbial processes in efforts to isolate contaminants [Cuthbert et al, 2013;Mountassir et al, 2014]. On the other hand, precipitation-induced permeability reduction within fault zones limits dissipation of increasing pore pressures, which can result in the undesired effect of more frequent seismic events [Audet and Burgmann, 2014;Yarushina and Bercovici, 2013].…”
Section: Introductionmentioning
confidence: 99%